Simulation data supporting Toward A-fs-meV Resolution in Electron Microscopy: Systematic Simulation of the Temporal Spread of Single-Electron Packets - Curtis, Wyatt, A; Flannigan, David J (My University, 2021)
This data contains the simulation output from General Particle Tracer to generate the figures in the related publication. See the related publication for detailed information on each dataset.
Data files containing the output of GPT simulations.